A theoretical study of the role of social media in promoting the cultural identity of high school students in light of Vision 2030 (The International Journal of Educational Sciences and Arts, 2026)
This theoretical study aims to analyze the role of digital media in promoting cultural identity among secondary school students in light of the objectives of Saudi Arabia's Vision 2030. Its importance stems from the significance of secondary school students as a crucial stage in shaping their cultural awareness and national belonging within the rapidly evolving digital environment and the effects of cultural globalization. The study employs a descriptive-analytical approach, analyzing literature and previous studies related to digital media and cultural identity. It also utilizes algorithmic culture theory to explain the role of digital algorithms in shaping cultural content on digital platforms.The study results showed that digital media is one of the influential factors in shaping students' cultural values ​​and attitudes, as it provides ample opportunities to disseminate cultural knowledge and promote national belonging through interactive digital content. Conversely, undirected use or intensive exposure to digital content may contribute to weakening some aspects of cultural identity. The study also highlighted the role of algorithms in personalizing digital content and directing users' cultural experience. The study confirms that employing digital media in a conscious and planned manner can support the strengthening of students' cultural identity, in line with the objectives of Saudi Vision 2030 in building human capital and consolidating national identity.Keywords: Digital Media, Cultural Identity, High School Students, Algorithmic Culture, Saudi Vision 2030.
Keywords: Digital Media; Cultural Identity; High School Students; Algorithmic Culture; Saudi Vision 2030